Design guidelines for stainless steel in piping systems (Designers' handbook series, 2020)
This publication presents information on the design, fabrication, installation and economy of stainless steel in piping systems. The guidelines presented contain important information for piping specialists and design engineers that will save money, time and effort in the several diverse industries utilizing piping systems.